2020
DOI: 10.1001/jamaoto.2019.4312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Associated With Favorable Outcomes in Adults With Bell Palsy

Abstract: Identification of the factors associated with improved facial nerve function after treatment of Bell palsy is important to provide patients with early and effective treatment. OBJECTIVE To identify factors that are associated with improved treatment outcomes in patients with Bell palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 53 publications
4
58
1
2
Order By: Relevance
“…The full recovery rate of females (72%) was similar to that of males (69%) [2]. Yoo et al showed that gender was not associated with a favorable outcome (OR, 1.04; 95% CI, 0.78 to 1.38) [12]. This finding was compatible with our study results showing that sex did not influence the final outcome or recovery time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The full recovery rate of females (72%) was similar to that of males (69%) [2]. Yoo et al showed that gender was not associated with a favorable outcome (OR, 1.04; 95% CI, 0.78 to 1.38) [12]. This finding was compatible with our study results showing that sex did not influence the final outcome or recovery time.…”
Section: Discussionsupporting
confidence: 91%
“…Peitersen showed that children (aged ≤ 14 years) had the most favorable prognosis, while older patients (aged > 60 years) had the worst outcomes [2]. Yoo et al reported that age younger than 40 years was associated with a favorable outcome [12]. In our study, age less than 60 years was not associated with favorable outcomes.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Therefore, the time to complete recovery and the effect of treatment are of great concern to patients. [ 26 ] With the introduction of KT, there is an effective method for the rehabilitation of PFP, its mechanism of action is as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections may also directly affect patients` facial nerve and thus lead to facial palsy. Viral cause in Bell`s palsy, if be treated promptly, higher number of patients will have their facial palsies, get dissolved freely [14]. Suggestions of bilateral facial palsy with the level of socioeconomic status, personal habits, mental status and poor hygiene have been considered [15] .Not all facial palsies respond to reanimation surgery, unless are highly chosen based on surgeons' decision for possible better results.…”
Section: Introductionmentioning
confidence: 99%